Strategic Capital Accumulation with Singular Control - Jan-Henrik Steg (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We present a duopoly model of strategic capital accumulation in continuous time with uncertainty, such that investment takes the form of singular control. Spot competition is of Cournot type. For this model there exists a parameterized and Pareto-rankable family of Markov perfect equiblibria in symmetric strategies, according to which implicit collusion induces positive option values. However, preemption can also eliminate any option value in a limiting case corresponding to Bertrand prices.
Keywords: C73; D43; D92; 330